Development of Seaweed (Padina tetrastromatica) incorporated Mince Sausage from Common Carp (Cyprinus carpio), reared in Inland Saline Water - Dharani M.; Amjad Khansaheb Balange (Journal of Indian Fisheries Association, 2023)
The study was conducted for the development of seaweed based value-added product from inland salinewater-reared common carp fish mince. Three concentrations of seaweed powder (0.5%, 1%, and 2%) wereused. The addition of 2% P. tetrastromatica powder to mince showed better results as compared to othertreatments. Compared to control sausages with 0% seaweed inclusion, the common carp mince sausages with2% seaweed powder addition had greater hardness values and ash content. Additionally, the sensory scores ofthe sausages that contain seaweed powder were satisfactory. Therefore, seaweed powder can be utilised as apotential component to enhance the dietary value and textural properties of fish mince sausages.Furthermore, developing value-added products will boost the market value of fish raised in inland saltwater,which are underutilised resources with a significant potential to expand aquaculture production.